Recombinant expression of hen egg white lysozyme with the assistance of xylanase fusion partner in Pichia pastoris. Issue 5 (2nd May 2022) - Cui, Lin; Huang, Huoqing; Zhang, Honglian; Wang, Xiaolu; Qin, Xing; Tu, Tao; Zhang, Jie; Su, Xiaoyun; Yu, Huimin; Bai, Yingguo; Luo, Huiying; Yao, Bin; et al.
ABSTRACT: Due to its bacteriolytic activity, hen egg white lysozyme (HEWL) is widely used in the feed, food, and pharmaceutical industries. However, its application is hindered by low protein expression levels in microbial expression systems. In this work, a novel fusion protein expression strategy was proposed for increasing the expression level of HEWL. First, HEWL, fused with a highly expressed fusion protein partner xylanase XynCDBFV, is expressed in Pichia pastoris . Secondly, a linker including endogenous protease cleavage sites was introduced between two fusion proteins in order to separate them directly during the secretion process. Finally, the results show that the supernatant of XynCDBFV-HEWL has a higher HEWL expression level and activity compared with HEWL only. It should be noted that the expression of HEWL reaches to about 3.5 g/L, and the activity of HEWL against Micrococcus lysodeikticus reaches to 1.50 × 10 5 U/mL in a fed-batch fermentation, which is currently the highest level of recombinant expression of an egg white-derived lysozyme. Taken together, we acquired bioactive HEWL for large-scale recombinant production in Pichia pastor is using a novel fusion protein expression strategy, which could then be used for a variety of applications. Graphical Abstract: uf0001